MANAJEMEN TRANSFORMASI PEMBELAJARAN DI SEKOLAH ALAM DEPOK: INTEGRASI MEDIA DIGITAL DAN PRAKTIK LAPANGAN - Putri, Tatia Rahmanita; Mumtazah, Muna; Andika, Taura; Lestari, Ambar Sri (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyzes Learning Transformation Management at Sekolah Alam Depok, focusing on the integration of digital media and field practices. The background highlights the need for learning innovations that combine technological advances with nature-based approaches, while respecting the school's limitations on gadget use by students. A qualitative method with a case study approach was employed, involving observations and interviews with teachers and students. The results indicate that Learning Transformation Management at Sekolah Alam Depok successfully integrates digital media with field practices, enhancing student motivation and engagement. Students showed greater enthusiasm in learning activities that combined technology and outdoor practices. The use of digital media, such as educational videos and interactive presentations, clarified the understanding of concepts taught, even without personal devices. This integration made learning more contextual, engaging, and meaningful the novelty of this research lies in an effective learning management model that combines non-device digital media with outdoor learning practices, creating an innovative and adaptive learning environment suitable for nature-based schools in the digital age. These findings are expected to serve as a reference for other schools in developing relevant learning strategies.